2006
DOI: 10.1111/j.1600-0447.2005.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the CAPE: a self‐report instrument for the measurement of psychotic experiences in the general population

Abstract: The results indicate that self-reported dimensions of psychotic experiences in general population samples appear to be stable, reliable and valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
367
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 462 publications
(379 citation statements)
references
References 42 publications
6
367
0
6
Order By: Relevance
“…The CAPE is a self-report instrument and captures variation in the positive and negative dimensions of nonclinical psychotic experiences as well as variation in depression. This scale was recently validated against clinical interview measures of schizotypy and psychosis-proneness (Konings et al, 2006). Previous work has shown that subclinical psychotic experiences measured with valid self-report questionnaires show longitudinal continuity with more severe states of psychosis, such as psychotic illness (Chapman et al, 1994;Hanssen et al, 2005) and are transmitted in families .…”
Section: Psychosis Measuresmentioning
confidence: 99%
“…The CAPE is a self-report instrument and captures variation in the positive and negative dimensions of nonclinical psychotic experiences as well as variation in depression. This scale was recently validated against clinical interview measures of schizotypy and psychosis-proneness (Konings et al, 2006). Previous work has shown that subclinical psychotic experiences measured with valid self-report questionnaires show longitudinal continuity with more severe states of psychosis, such as psychotic illness (Chapman et al, 1994;Hanssen et al, 2005) and are transmitted in families .…”
Section: Psychosis Measuresmentioning
confidence: 99%
“…The positive dimension of the CAPE (18 self-report items), based on the Peters et al Delusions Inventory (Peters et al 1999) and modified to also include hallucinatory experiences, was used to assess lifetime subclinical positive psychotic experiences (Stefanis et al 2002;Konings et al 2006). Each CAPE item rates the frequency of subclinical psychotic experiences on a four-point scale; scores can thus range from 18 to 72, and higher scores indicate more subclinical psychotic experiences.…”
Section: Instrumentsmentioning
confidence: 99%
“…low mood and negative cognitions). The CAPE has been validated in clinical and non-clinical samples and found to reliably assess positive, negative and depressive symptoms (Hanssen et al, 2003; Konings, Bak, Hanssen, Van Os, & Krabbendam, 2006). …”
Section: Methodsmentioning
confidence: 99%